Acute Inferior Myocardial Infarction: Beyond the ST-Segment Elevation - Rocha, Diana (2024)
Acute coronary syndromes (ACS) are considered a continuum, enclosing both non-ST-elevation (NSTE)-ACS, including unstable angina and non-ST-elevation myocardial infarction (NSTEMI), and ST-elevation myocardial infarction (STEMI). The diagnosis of myocardial infarction (MI) is associated with troponin release. Classification of MI has fundamentally been based on the presence or absence of ST-segment elevation (STE) on the electrocardiogram (ECG). STE is a poor surrogate for acute coronary occlusion (ACO) causing MI. Mounting evidence suggests that a substantial fraction of patients presenting with NSTEMI have an ACO of their culprit artery. Due to a lack of classic ECG findings, these NSTEMI patients, despite ACO of the culprit artery, may be missed, leading to either delay in or no revascularization. This case report highlights one specific pattern potentially identifying ACO that does not meet STEMI criteria, the Aslanger pattern. Early identification of this NSTEMI pattern potentially accelerates revascularization.